Sharps injuries among medical students in the faculty of medicine, Colombo, Sri Lanka - Liyanage, I.K.; Caldera, T.S.K.R.D.; Rajapaksha, R.W.M.A.; Liyange, C.K.; De Silva, P.; Karunathilake, I.M. (International Journal of Occupational Medicine and Environmental Health, 2012)
Introduction: Medical students undertake clinical procedures which carry a risk of sharps injuries exposing them to bloodborne infections. Objectives: To study the prevalence and correlates of sharps injuries among 4th-year medical students in the Faculty of Medicine, University of Colombo, Sri Lanka. Materials and Methods: The survey was conducted among 4th-year medical students to find out the incidence of injuries during high-risk procedures, associated factors and practice and perceptions regarding standard precautions. A self-administered questionnaire was administered to a batch of 197 4th-year medical students. Results: A total of 168 medical students responded. One or more injury was experienced by 95% (N = 159) of the students. The majority (89%) occurred during suturing; 23% during venipuncture and 14% while assisting in deliveries. Most of the incidents (49%) occurred during Obstetrics and Gynecology attachments. Recapping needles led to 8.6% of the injuries. Thirty-five percent of students believed they were inadequately protected. In this group, adequate protection was not available in 21% of the incidences and 24% thought protection was not needed. Following the injury, 47% completely ignored the event and only 5.7% followed the accepted post-exposure management. Only 34% of the students knew about post-exposure management at the time of the incident. Only 15% stated that their knowledge regarding prevention and management was adequate. The majority (97%) believed that curriculum should put more emphasis on improving the knowledge and practice regarding sharps injuries. Conclusions: The incidence of sharps injuries was high in this setting. Safer methods of suturing should be taught and practiced. The practice of standard precautions and post-injury management should be taught.
Keywords: Sharps injury; Medical students occupational safety; Needle-stick injuries